hubungan ansietas dengan kualitas tidur lansia hipertensi diwilayah puskesmas UPTD indra giri hilir - Ramadia, Arya; Valentino, Febrian; Rahmaniza, Rahmaniza (Jurnal Ilmu Keperawatan, 2023)
Elderly is a natural process that cannot be avoided by every individual in the final phase of human development. The high number of elderly and the problems faced by them are also getting higher, especially in experiencing high levels of anxiety caused by various factors such as thinking about advancing age and how it has an impact on the inability to meet needs and think about problems that occur in the family. Along with experiencing a high level of anxiety, it has an impact on the quality and sleep pattern of the elderly, which consists of two aspects, namely good and bad, resulting in various kinds of possibilities for the elderly experiencing health problems. The purpose of this study was to determine the relationship between anxiety and sleep quality in elderly people with hypertension at the Pekan Heran Health Center, Rengat Barat District, and Indragiri Hulu Regency. The type of research used in this research is quantitative with descriptive correlation using a cross-sectional design. The number of samples is 108, and the sampling technique in this study is purposive sampling. The results showed that most of the anxiety in the elderly was in the moderate category, with 41 respondents (38.0%). Most of the sleep quality of elderly hypertensives is in the good category, according to 61 respondents (56.5%). Anxiety has a relationship with the sleep quality of the elderly with hypertension, where there is a p value of 0.000. Health workers at the Puskesmas are advised to be able to explore family support for the elderly so that they can help maintain sleep quality in elderly hypertensives.